Mass spectrometry-based protein assays for in vitro diagnostic testing. (April 2012) - Nedelkov, Dobrin
Mass spectrometry-based protein assays hold great promise for in vitro diagnostic testing. Technological advances in mass spectrometry have given rise to instruments and methods that are fully capable of automated and high-throughput protein assaying. Yet, the numerous steps involved in such assays can lead to difficulties in assay characterization and validation, and can also make them unnecessarily complex and prohibitively expensive for everyday use. Simplification of both approaches and instrumentation seems to be the solution to the fast introduction of the mass spectrometry-based assays into the clinical laboratories. One such simplified approach is the mass spectrometric immunoassay, which couples targeted immunoaffinity protein separation with the power of mass spectrometry detection. Several mass spectrometric immunoassays have been extensively characterized and have found their way into clinical laboratory improvement amendments-certified laboratories in the form of laboratory developed tests. Reviewed in this special report is the development and validation of one of those assays – a Cystatin mass spectrometric immunoassay. With the added advantage of protein variant detection and quantification, these assays can redefine our view of protein diversity, with clear implications in biomarker discovery, validation, and ultimately, in vitro diagnostic testing.